Great writing. - Folse, Keith S; Pugh, Tison (Boston: National Geographic Learning, 2020)
Now with engaging National Geographic images, the new edition of the Great Writing series helps students write better sentences, paragraphs, and essays. Great Writing 5 now also prepares students to write research papers with clear explanations, student writing models, and meaningful practice opportunities and prepares writers for college-level research papers with instruction in citing sources, paraphrasing, summarizing, and synthesizing.
Reviewing an essay -- The writing process -- Using original sources -- Cause-effect essays -- Comparison essays -- Reaction essays -- Argument essays -- The research paper?
Includes index.
Keywords: English language -- Rhetoric -- Problems, exercises, etc; Essay -- Authorship -- Problems, exercises, etc; Report writing -- Problems, exercises, etc